Beneficial Effects of Implementing Stroke Protocols Require Establishment of a Geographically Distinct Unit. Issue 12 (December 2015) - Akhtar, Naveed; Kamran, Saadat; Singh, Rajvir; Cameron, Peter; D'Souza, Atlantic; Imam, Yahya; Bourke, Paula; Joseph, Sujatha; Khan, Rabia; Santos, Mark; Deleu, Dirk; El-Zouki, Abdel; et al.
Abstract : Background and Purpose—: Usefulness of multidisciplinary stroke units in acute stroke patients is well established. There is extensive western literature on usefulness of stroke units in outcome, but limited evidence from the rest of the world. We aim to evaluate the impact of establishing a stroke unit on outcome in patients presenting to a tertiary care facility. Methods—: This is a retrospective study of 1003 patients with acute stroke admitted to Hamad General Hospital, Qatar, between January 2014 and February 2015. Patients directly admitted to intensive care unit (132) were excluded. We compared outcomes of pre- and poststroke ward (SW) establishment and in SW patients versus those of general medical wards. Results—: Before the establishment of the SW, 175 patients were admitted to the hospital. From April 2014 to February 2015, 696 patients were admitted (SW, 545; medical ward, 151). There was a significant reduction in length of stay from 14.7±27.7 to 6.2±20.2 days ( P =0.0001) and incidence of complications (23.6% versus 6.4%, P =0.0001) after implementation of stroke-specific protocols. Prognosis at discharge (modified Rankin Scale 0–2 in 56.0% versus 70.4%, P =0.001) and at 90 days (modified Rankin Scale 0–2 in 70.6% versus 95.0%, P =0.001) also significantly improved. Compared with medical ward patients, outcome was significantly better in SW patients with fewer complications (10.9% versus 5.0%, P =0.013) and shorter length of stay (8.9±30.7 versus 5.4±16.1 days, P =0.05). Conclusions—: Establishing a distinct SW is essential for achieving full benefits of stroke protocols implementation. SW patients have significantly fewer complications and better prognosis when compared with patients in medical wards. Abstract : Supplemental Digital Content is available in the text.